Theology Of A Classless Society - Geevarghese, Mar Osthathios (Maryknoll, N.Y : Orbis Books, 1979)
Includes bibliographical references and index. Metropolitan of the Orthodox Syrian Church in Kerala, 1918-
Keywords: Christian sociology; Social classes -- Moral and ethical aspects